PENGARUH VIDEO FUN LEARNING CONSONANT TERHADAP KEMAMPUAN PRA MEMBACA ANAK USIA 4-5 TAHUN DI TK ADVENT 2 MEDAN - Vanny Natalsha Damanik; Srinahyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to determine the effect of Fun Learning Consonant videos on the pre reading abilities of children aged 4-5 years at TK Advent 2 Medan. The study employed a quantitative approach using a pre-experimental design with a one-group pretest posttest design. The research subjects consisted of 15 children aged 4-5 years. Data were collected through structured observation using a pre reading ability observation sheet. The indicators measured included recognizing letter symbols, recognizing letter sounds, and associating letter sounds with letter symbols. Data analysis was conducted using descriptive statistics and the Wilcoxon Signed Rank Test. The results showed that the average pretest score was 19.53, while the average posttest score increased to 28.40, with a difference of 8.87 points. The Wilcoxon test yielded a significance value of 0.001 (p<0.05), indicating a significant difference between pretest dan posttest scores. These findings demonstrate that the Fun Learning Consonant video has a significant effect on improving the pre reading abilities of children aged 4-5 years at TK Advent 2 Medan.